The Effect of DNA Extraction Methods on Observed Microbial Communities from Fibrous and Liquid Rumen Fractions of Dairy Cows - Vaidya, Jueeli D.; van den Bogert, Bartholomeus; Edwards, Joan E.; Boekhorst, Jos; van Gastelen, Sanne; Saccenti, Edoardo; Plugge, Caroline M.; Smidt, Hauke (Frontiers in Microbiology, 2018)
DNA based methods have been widely used to study the complexity of the rumen microbiota, and it is well known that the method of DNA extraction is a critical step in enabling accurate assessment of this complexity. Rumen fluid (RF) and fibrous content (FC) fractions differ substantially in terms of their physical nature and associated microorganisms. The aim of this study was therefore to assess the effect of four DNA extraction methods (RBB, PBB, FDSS, PQIAmini) differing in cell lysis and/or DNA recovery methods on the observed microbial diversity in RF and FC fractions using samples from four rumen cannulated dairy cows fed 100 % grass silage (GS100), 67 % GS and 33 % maize silage (GS67MS33), 33 % GS and 67 % MS (GS33MS67), or 100 % MS (MS100). An ANOVA statistical test was applied on DNA quality and yield measurements, and it was found that the DNA yield was significantly affected by extraction method (p < 0.001) and fraction (p < 0.001). The 260/280 ratio was not affected by extraction (p = 0.08) but was affected by fraction (p = 0.03). On the other hand, the 260/230 ratio was affected by extraction method (p < 0.001) but not affected by fraction (p = 0.8). However, all four extraction procedures yielded DNA suitable for further analysis of bacterial, archaeal and anaerobic fungal communities using quantitative PCR and pyrosequencing of relevant taxonomic markers. Redundancy analysis (RDA) of bacterial 16S rRNA gene sequence data at the family level showed that there was a significant effect of rumen fraction (p = 0.012), and that PBB (p = 0.012) and FDSS (p = 0.024) also significantly contributed to explaining the observed variation in bacterial community composition. Whilst the DNA extraction method affected the apparent bacterial community composition, no single extraction method could be concluded to be ineffective. No obvious effect of DNA extraction method on the anaerobic fungi or archaea was observed, although fraction effects were evident for both. In summary, the comprehensive assessment of observed communities of bacteria, archaea and anaerobic fungi described here provides insight into a rational basis for selecting